Batman : the multiverse of the Dark Knight : an illustrated guide - Manning, Matthew K. (Insight editions, 2023)
Take a tour through the diverse worlds of the DC Multiverse in this comprehensive guidebook detailing the lives of its many Caped Crusaders. Dive into different dimensions and meet countless variations of the Dark Knight--from the Batman Who Laughs to Flashpoint Batman, from Captain Leatherwing to Bizarro-Batman, this book profiles more than 60 iconic iterations of DC's legendary Super Hero alongside striking original art.